HUBUNGAN ANTARA PENDIDIKAN KARAKTER DENGAN KECERDASAN SOSIAL SISWA KELAS V SDN GUGUS V KECAMATAN CAKRANEGARA - Bq Weddayu Murferatiwi; Darmiany Darmiany; Khairun Nisa (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
Learning in the 21st century must be able to develop competitive skills that focus on developing higher order thinking skills, one of which is critical thinking. Therefore we need a basic teaching skill of teachers in order to develop the quality of learning one of which is the teacher asking questions. This study aims to determine whether there is a relationship between the teacher's questioning skills and the critical thinking skills of class V students of Cakranegara group 3 2018/2019 academic year. This research uses a quantitative approach with a descriptive correlational type. The subjects in this study were fifth grade students in Cluster III Cakranegara with a population of 130 students. Samples were taken randomly using a simple random sampling type probability sampling technique to obtain 65 students. Data collection techniques used were questionnaire and multiple choice tests. While the data analysis technique is the Pearson product moment correlation by using the SPSS 16.0 program. Based on the results of data analysis, it was found that the value of sig (2-tailed) 0.00 <0.05, which means it can be said to be significant and there is a relationship between the teacher's questioning skills and students' critical thinking skills. Based on this research, principals and teachers need to support and develop students' critical thinking skills through the teacher's questioning skills well.